Mastering machine learning with Spark 2.x : create scalable machine learning applications to power a modern data-driven business using Spark /: create scalable machine learning applications to power a modern data-driven business using Spark. (2017) - Tellez, Alex; Pumperla, Max; Malohlava, Michal
No abstract available